A Rare Instance of Chordoid Glioma With Large Calcification Mimicking Craniopharyngioma. Issue 2 (March 2020) - Cui, Zhenwen; Mu, Cuiping; Yang, Fengyu; Li, Huanting; Liu, Wei; Feng, Yugong
Abstract : Abstract: Chordoid glioma (CG) is a world health organization classified grade II tumor whose typical localization is in the anterior part of the third ventricle. It's clinical, neuroimaging, and pathologic features may vary and furthermore mimic other types of benign lesions usually associated with a better outcome, thus representing a potential radiological and diagnostic pitfall. In this article, the authors present a novel case of a 51-year-old male who underwent gross total removal of the tumor of the third ventricle with high calcification. The imaging studies and the intraoperative examination led at first to a hypothesis of craniopharyngioma. In this case, the patient underwent successful operative management and has remained well throughout follow-up.